Stability mechanisms of soft rock mining roadways through roof cutting and pressure relief: an exploratory model experiment - Zhu, Qingwen; Li, Tingchun; Lou, Qingnan; Liu, Yishuai; Li, Chunping; Chen, Jiangang (Frontiers in Ecology and Evolution, 2023)
Soft rock mining roadways are severely deformed and damaged during coal mining. Blindly increasing the support strength not only has little effect but also wastes material resources. Maintaining the original support parameters, model experiments were conducted to investigate the mechanism of pressure relief protection of the front soft rock mining roadway by cutting the roof behind the longwall face. The roof-cutting height was 2.5 times the coal thickness, the angle was 10°, and the advance distance is 0. The study found that the abutment stress borne by the roof of the original roadway was transferred to the coal seams to be mined. The average stress of the coal seams increased by 10%, while the average stress of the surrounding rock in the front roadway decreased by 12.57%. The roof cutting weakened the influence of the overlying strata in the gob on the rear roadway. The stability of the rear roadway also weakened the traction effect on the front roadway. The vertical convergence of the front roadway decreased by 27.3%, and the deformation of the coal pillars decreased by 15.7%. The roof cutting reduced the stress of the front roadway to the peak failure stress, fundamentally weakening the main factor that induced the deformation of the front roadway. Numerical simulations were performed to research the deformation and stress distribution properties of the surrounding rock after roof cutting, and the model experimental results were validated. Finally, engineering recommendations are presented, which are expected to provide a reference for controlling the roadway stability of soft rock masses.